First record of the twostripe goby, Valenciennea helsdingenii (Gobiidae, Gobiiformes) from the southeast coast of India - Kannan, K. (Pensoft Publishers, 2013)
Abstract. Two specimens of Valenciennea helsdingenii (Bleeker, 1858) were collected off Punnakayal coast, from Gulf of Mannar, southeast coast of India in November 2012. The morphometric and meristic characters of the recorded specimens are described and discussed. This is the first record of the species from the Indian waters that is a range extension of its known range within the Indian Ocean.